ANALISIS FAKTOR-FAKTOR INTERNAL YANG MEMPENGARUHI PEMBIAYAAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) PADA BANK SYARIAH DI INDONESIA - Destiana, Rina (Jurnal Riset Keuangan dan Akuntansi, 2016)
It is a fact that the UMKMÃ¢â‚¬â„¢s are resistant due to monetary crisis in Indonesia. It proves UMKMÃ¢â‚¬â„¢s significant and important roles of the economic development in establishing employment, improving National Gross Domestic Product and developing national industries. Because of these potentials of UMKMÃ¢â‚¬â„¢s, banks should provide assistantships by providing their loan as financial aids. It is however, influenced by some factors such as internal and external factors. The aim of this research was to analyze the influence of internal factors which refers to internal bank condition such as third party funds (DPK), capitals, profitability, risk and liquidity toward UMKMÃ¢â‚¬â„¢s at syaria banking in Indonesia. The data of the study were taken from general syaria bank (BUS) and syaria business unit (UUS) which were provided in the syaria banking statistic from Indonesian central bank (official website of BI) from 2008 up to Juni 2013. Due to the limited data provided in syaria banking statistic, the 2008 and 2009 data were three-monthly: March, June, September and December while the 2010 to Juni 2013 data were monthly. Thus, there were 50 time series of observation. The data were analyzed by using regression provided in 17.0 ver. SPSS. The result of regression test shows that internal factors which significantly influenced UMKMÃ¢â‚¬â„¢s finance at syaria banking were the DPK and liquidity, whereas the other factors such as the capital, profit and risk had no significance on the financing UMKMÃ¢â‚¬â„¢s.Ã‚Â